(untitled) (Research, Society and Development, 2017)
The aim of this paper is to present a sample about the public instruction in Cidade do Príncipe, based on the information made available in the Provincial Reports of the Rio Grande do Norte in the corresponding period from 1870 to 1889, the final years of the Empire. Methodologically we performed a bibliographical research, studying the writings of classics authors of history as Demerval Saviani and José Ricardo Pires de Almeida; authors that studied the Seridó region in its different aspects, including the educational, as Muirakytan K. de Macêdo, Olavo Medeiros Filho and Olívia Medeiros Neta/ theses and dissertations; other written sources as the Law and Provincial Reports. From this bibliographical and sources survey, the data were crossed and this allowed us a perception, although initial, of the school educational scenario in Seridó. In this survey it was possible understand that the trigger of the public instruction in the region was still something little encouraged in face of the found records in the Reports. Therefore, the first impressions realized highlight that the education in the region of Cidade do Príncipe in the studied period was still mainly based on teaching the precepts of moral and Christian doctrine.